Narrowing abdominal aorta and vein is a simple and useful method for preparing a mice model of gestational hypertension. Issue 4 (April 2019) - Yasui, Yuri; Kumasawa, Keiichi; Minato, Kenji; Nakamura, Hitomi; Kimura, Tadashi
Abstract: Hypertensive disorder of pregnancy (HDP) is a major cause of maternal morbidity and mortality, fetal growth restriction (FGR), and premature delivery. Soluble fms-like tyrosine kinase-1 (sFLT-1) is significantly elevated in pre-eclamptic women. Making animal models of hypertensive pregnancy is costly and requires advanced equipment. We established a gestational hypertension (GH), one of the HDP subtypes, mouse model by narrowing the abdominal aorta and vein together with a medical drip tube on day 10.5 of gestation. Systolic and diastolic blood pressure on day 18.5 of gestation in the narrowed aorta and vein (NAV) group were significantly higher than those in the control group. Fetal weight decreased in the NAV group. Serum sFLT-1 was significantly increased in the NAV group on day 18.5 of gestation compared to the control group. After delivery, blood pressure and serum sFLT-1 level did not differ between the NAV and the control groups. These parameters normalized postpartum. We established a novel GH mouse model through an easy operative procedure using a simple device. In this NAV model, blood pressure and serum sFLT-1 level were increased on day 18.5 of gestation, and normalized promptly after delivery. The mouse model mimics human GH, and is suitable for the development of other treatments.